Precision micro-spray tower for application of entomopathogens - Mascarin, Gabriel Moura (BioAssay, 2013)
An inexpensive, portable and easy handling spraying device was developed to apply several entomopathogens in dose-response bioassays. The micro-sprayer was calibrated using different settings of pressure and time to apply a wide range of doses on a plain surface. Filter paper cards sprayed with dye solutions were used to examine the deposition uniformity. Also, the relationship between conidial suspensions of fungal entomopathogens and dose applied was determined. As a result, the combination of 10 PSI and 3 s provided the most uniform coverage and applied a volume of 2.15 µL cm-2 (= 215 L ha-1) and dose of 150 conidia mm-2(= 1012 conidia ha-1) at a concentration of 1×107conidial mL-1.